Comparative Risk of Surgical Site Infection With Open Cholecystectomy Vs Laparoscopic Cholecystectomy - Aslam, Rashid; Siddique, Abu Bakar; Muhammad Kalim; Faridoon, Shehla; Shah, Rehmat Ullah; Khan, Shehzad Akbar (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: This study aimed to compare the risk of surgical site infection with open vs laparoscopic cholecystectomy. METHODOLOGY: This randomized control trial was done at the Department of Surgery, Hayatabad Medical Complex, Peshawar, for 12 months from 11/5/2018 to 11/5/2019. 116 patients were recruited for this study, 58 for each group randomly allocated to a group by lottery method and concealed Allocation. Patients in Group A underwent laparoscopic cholecystectomy, while patients in group B underwent open cholecystectomy. According to ward protocol, post-operative analgesia & antibiotics were given to patients in both groups. Expert consultant general surgeons did all the evaluation & procedures; all the patients were followed up to 30 days after the procedure & any surgical site infections, if found, were noted. RESULTS: The mean age was 36 years ± 12.19 SD and 38 years ± 11.88 SD in laparoscopic and open cholecystectomy, respectively. In laparoscopic cholecystectomy, 28% of patients were male, and 72% of patients were female, while in open cholecystectomy, 29% of patients were male, and 71% of patients were female. 07% of laparoscopic and 26% of open cholecystectomy patients had surgical site infections. CONCLUSION: Our study concludes that the frequency of surgical site infection was found less in laparoscopic cholecystectomy than in open cholecystectomy.